Dis-placing the world: Nomadic politics in Mona Hatoum’s living cartographies of passages - Tzelepis, Elena (The Greek Review of Social Research, 2013)
The present essay draws from contemporary art and particularly from the art of the diasporic artist Mona Hatoum. Hers is an art about a corporeal subjectivity attuned to a living cartography of passages between Palestine, Lebanon, and England. I explore her art work with intersecting cartographies and corporealities, by focusing on her artistic gestures of displacing established notions of “home” and the “world”, in all their gendered implications. I try to unravel the ways in which Mona Hatoum keeps us on the alert for the hierarchies of false and abstract universalism, while, at the same time, keeps open the promise (and the question) for the potential subversiveness of “foreignness” and “belonging”.